WAYS TO REDUCE FOOD WASTE AT THE LEVEL OF HOSPITALITY AND CONSUMER INSTITUTIONS - TEODOROVYCH, Larysa; KYIANYTSIA, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Against the background of the COVID-19 pandemic and military action in Ukraine, there is an acute shortage of food in the world and this figure continues to grow. The poor social strata of the middle- and even highly developed groups of the country found themselves in a difficult situation. At the same time, 17 percent (1.3 billion tons) of total world food production is wasted, many products are thrown away, forming food waste that negatively affects the state of the environment and can irreversibly change its quality. A significant amount of food is lost in retail and consumption. This amount of food is enough to feed 2 billion people. Such waste is estimated to cost the world economy more than 1 trillion a year. Reducing per capita food waste at the level of retail, hospitality and consumers themselves is important for food security and the transition to a resource-efficient economy. The classic linear model of product production can be replaced by a closed-loop economy that focuses on products and services that minimize waste and other types of pollution. A significant project of the closed-loop economy is Farm to Fork. The initiative acts as a link between all sectors of the food industry. A number of state and public initiatives are in place to prevent the negative consequences of irresponsible eating habits and to avoid the threat of hunger. Many countries around the world have established rules for restaurants and free food shops to food banks or charities. In order to reduce food losses in the world, there are three largest food banking networks: Global Food Banking Network (GFN), Feeding America - in the US and the European Federation of Food Banks; public initiatives are spreading; various volunteer programs provide tools that restaurants can use to achieve this goal, tracking their own costs; software will help to control food stocks and store products in hospitality establishments. Responsible consumption of food by the population, which is based on proper and balanced nutrition, will significantly reduce the amount of food wasted, so educational work with consumers is extremely important. Ukraine needs to develop clear programs aimed at reducing food waste and responsible consumption. Therefore, an effective food waste reduction strategy must take into account supply, demand, operations and outlets. It should be based on the participation in this process of the state (at the legislative level), entrepreneurs (at the level of production and services), as well as consumers (understanding and support of public initiatives, personal behavior with food).